Ministry of Trade and Industry Decree No. 186 For The Year 2019 = وزارة التجارة والصناعة قرار رقم 186 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic